Utilization of Micro-lecture Videos in Teaching Selected Microbiology Laboratory Topics (American Journal of Multidisciplinary Research and Innovation, 2025)
The sudden shifting of classes to online class set-up is ineluctable in Philippine education today due to many events and adverse environmental conditions. Laboratory courses are most affected by the limited procedural videos that are explicitly developed and target the students of the current generation, particularly microbiology laboratory procedures. Hence, this study utilized developed instructor-made micro-lecture videos (IMMV) of selected microbiology laboratory topics (Culture Media Preparation and Gram Staining) as supplementary materials in a blended-learning asynchronous class set-up. A mixed method-explanatory sequential was used with 54 Medical Biology students through a validated pre-test, post-test, and survey. Through a paired t-test, the pre- and post-test scores of the experimental group revealed significant differences in their scores. Moreover, an independent t-test was used to analyze the post-test scores of the control and experimental groups, which revealed a significant difference in their performance. Students perceived that utilizing IMMV positively affects their academic performance in terms of control over the learning process, knowledge retention, and intrinsic motivation. As such, IMMVs are brief, concise, time-efficient procedures, effective guides for learning, provide sufficient learning, developed with encouraging and motivating content, captivate learners’ attention and interest, create a significant learning impact for students, promote advanced learning efficiency, and provide convenience for student’s learning. This suggests that learning microbiology laboratory topics through micro-lecture befits the needs and learning styles of the generation of learners today sufficiently and effectively.